2013
DOI: 10.1063/1.4816463
|View full text |Cite
|
Sign up to set email alerts
|

The effect of thermal treatment induced inter-diffusion at the interfaces on the charge trapping performance of HfO2/Al2O3 nanolaminate-based memory devices

Abstract: The charge trapping memory devices based on different HfO2/Al2O3 nanolaminated charge trapping layers were prepared and investigated. The memory device with 6 interfaces HfO2/Al2O3 shows a memory window of 4.7 V in its capacitance-voltage curve and a better retention property. It was suggested that the thermal treatment would reduce the defects inside the bulk HfO2, but cause an inter-diffusion at the interface HfO2/Al2O3, which could create additional defects at HfO2/Al2O3 interface. Increasing the number of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 56 publications
(27 citation statements)
references
References 27 publications
1
26
0
Order By: Relevance
“…22,23 When V g is swept toward a high positive value, electrons can tunnel through the 3 nm-thick Al 2 O 3 barrier into HfO 2 charge trapping layer by means of Fowler-Nordheim (FN) tunneling. 24,25 The resultant accumulation of electrons in HfO 2 trapping layer screens the control-gate electric field to reach the silicon channel, which results in a positive shift of the threshold voltage. When V g is swept from the positive to the negative direction, however, electrons are transferred back from the HfO 2 charge trapping layer to the channel; simultaneously holes tunnel through the barrier and are trapped in the HfO 2 layer which causes the threshold shifting to the negative direction.…”
Section: Resultsmentioning
confidence: 99%
“…22,23 When V g is swept toward a high positive value, electrons can tunnel through the 3 nm-thick Al 2 O 3 barrier into HfO 2 charge trapping layer by means of Fowler-Nordheim (FN) tunneling. 24,25 The resultant accumulation of electrons in HfO 2 trapping layer screens the control-gate electric field to reach the silicon channel, which results in a positive shift of the threshold voltage. When V g is swept from the positive to the negative direction, however, electrons are transferred back from the HfO 2 charge trapping layer to the channel; simultaneously holes tunnel through the barrier and are trapped in the HfO 2 layer which causes the threshold shifting to the negative direction.…”
Section: Resultsmentioning
confidence: 99%
“…3(b), the planar density of the trapped charges at an applied gate voltage of ±13 V is estimated as 5.37 × 10 12 cm −2 , a little lower than that annealed at 200 • C. It means that the post annealing in N 2 can slightly reduce the density of the defects in Hf 0.5 Zr 0.5 O 2 films. Due to the possible inter-diffusion at the interface Al 2 O 3 /Hf 0.5 Zr 0.5 O 2 during the post-annealing process at high temperature, 20 the further annealing process at higher temperature was avoided.…”
Section: Resultsmentioning
confidence: 99%
“…A charge-trapping memory (CTM) structure was designed to measure the density of the defect states in Hf 0.5 Zr 0.5 O 2 film, 20 as schematically shown in Fig. 1, in which Al 2 O 3 films are employed as the tunneling layer and the blocking layers, and the charge-trapping layer is Hf 0.5 Zr 0.5 O 2 film.…”
Section: Methodsmentioning
confidence: 99%
“…21 It was also reported that the multilayered high-k charge-trapping layer, such as HfO 2 /Al 2 O 3 /HfO 2 and ZrO 2 /Al 2 O 3 /ZrO 2 etc., causes an enhancement of the charge-storage efficiency of the CTM devices. [22][23][24][25][26] In our previous study, a remarkable charge-trapping efficiency and a fast programming/erasing(P/E) speed were obtained in a CTM device with a TiAlO high-k composite chargetrapping dielectric, achieving a density of trapped charges of 9.3×10 20 …”
Section: -14mentioning
confidence: 99%